WhatsApp messenger as a tool to supplement medical education for medical students on clinical attachment. Issue 1 (December 2017) - Raiman, Lewis; Antbring, Richard; Mahmood, Asad
Abstract Background Instant messaging applications have the potential to improve and facilitate communication between hospital doctors and students, hence generating and improving learning opportunities. This study aims to demonstrate the feasibility and acceptability of instant messaging communication to supplement medical education for medical students whilst on clinical attachment. Methods A total of 6 WhatsApp Messenger (WhatsApp Inc.) groups were created for medical students on clinical attachment. These were used to provide communication within Problem Based Learning (PBL) groups for a duration of 8 weeks. The frequency and type of communication were recorded. Students' opinions were evaluated through a structured interview process at the end of the study period. A thematic analysis was performed on the content of the instant messaging groups and on the results of the structured interviews. Results All of the participants were active in their respective messaging groups (19 students and 6 tutors). A total of 582 messages, 22 images and 19 webpage links were sent. Thematic analysis on content of the instant messaging groups identified the following themes: organisational, educational and social. Thematic analysis on the content of interviews identified themes such as the ease of use of instant messaging, benefit of instant messaging to foster understanding and learning, and the ability to access recorded discussions. Conclusion The findings of this study illustrate a method by which communication within PBL groups can be facilitated by the use of instant messaging. The results indicate the feasibility and acceptability of WhatsApp Messenger in supplementing PBL teaching for medical students, and provides a framework for studies to investigate use amongst larger cohorts of students.